Trends and cross-country inequalities in the global burden of neurodevelopmental disorders among children aged 0–14 from 1990 to 2021 - Jia, Tian; Kong, Yezi; Zhao, Guna; Wang, Yu (Frontiers in Public Health, 2025)
BackgroundTo evaluate the trends and cross-country inequalities of three common neurodevelopmental disorders (NDDs): Autism spectrum disorders (ASD), Attention-deficit/hyperactivity disorder (ADHD) and Idiopathic developmental intellectual disability (IDID) among children aged 0–14, and further predicted its changes to 2046.MethodsThe estimates and their 95% uncertainty interval (UI) for prevalence of ASD, ADHD and IDID among children aged 0–14 across 204 countries were extracted from Global Burden of Disease (GBD) 2021. Joinpoint regression analysis was used to calculate the average annual percentage changes (AAPC). The slope index of inequality (SII) and concentration index recommended by the World Health Organization (WHO) are two standard indicators for measuring absolute and relative gradient inequality. Our study used these two indicators to quantify the inequality of this three common NDDs burden between countries with different Sociodemographic Index (SDI). Finally, we used the Nordpred model to predict the disease burden of NDDs in 2046.ResultsThe AAPC (95% confidence interval [CI]) in prevalence of the three common NDDs among children aged 0–14 worldwide from 1990 to 2021 were as follows: ASD 0.09 (0.08 to 0.09), ADHD −0.08 (−0.12 to −0.04) and IDID −0.86 (−0.88 to −0.84). The SII (95% CI) changed from 27.09 (−29.98 to 84.17) in 1990 to 38.36 (−21.48 to 98.20) in 2021 for ASD, from 1402.78 (1100.25 to 1705.31) in 1990 to 1402.76 (1083.55 to 1721.97) in 2021 for ADHD, from −594.52 (−755.05 to −434.00) in 1990 to −545.94 (−673.19 to −418.69) in 2021 for IDID. The concentration index (95% CI) showed 0.15 (0.07 to 0.23) in 1990 and 0.19 (0.10 to 0.26) in 2021 for ASD, 0.07 (−0.02 to 0.16) in 1990 and 0.02 (−0.07 to 0.11) in 2021 for ADHD, 0.44 (0.34 to 0.53) in 1990 and 0.39 (0.28 to 0.48) in 2021 for IDID. Compared to 2021, the age-standardized prevalence rates (ASPR) in 2046 of the three common NDDs showed a slight decrease in ASD and ADHD, a slight increase in IDID.ConclusionAs a major public health concern, the global burden of NDDs in children exhibited distinct trends from 1990 to 2021: an increasing trend for ASD, and decreasing trends for ADHD and IDID. Health inequalities persist across these conditions. The burdens of ASD and ADHD are primarily concentrated in high-SDI countries/territories, whereas the burden of IDID is more prevalent in low-SDI countries/territories. Therefore, targeted public health strategies and equitable allocation of healthcare resources are essential to effectively mitigate the burden of NDDs.